Aerogel felt and preparation method thereof, battery and electric device

By using aerogel felt on lithium-ion batteries, the porous structures of silica aerogel and fiber felt filled with phase change materials is solved, and the problems of phase change material leakage and thermal runaway are achieved, and efficient battery cooling and temperature are achieved Uniformity reduces fire risk.

CN119153843APending Publication Date: 2024-12-17ANHUI ZHONGKE HENGAN SAFETY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411122695.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing phase change materials are prone to leakage problems in lithium-ion battery thermal management systems, and the battery module has low energy density, which fails to effectively inhibit the spread of heat, resulting in poor cooling effect and high fire risk.

Method used

Aerogel felt is used to fill phase change materials in the porous structure of silica aerogel, sunscreen and fiber felt to form a sealed heat storage layer, improve the thermal conductivity and latent heat of phase change, prevent heat propagation and Reduce fire risk.

Benefits of technology

Effectively reduce the temperature of the battery module, improve temperature uniformity, inhibit the spread of heat, reduce fire risk, and significantly cool down during fast charging and discharge, improving the cooling effect of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153843A_ABST
    Figure CN119153843A_ABST
Patent Text Reader

Abstract

The invention discloses an aerogel felt and a preparation method thereof, a battery and a power utilization device, the aerogel felt is applied to a lithium ion battery, the aerogel felt comprises a main body, the main body is provided with a porous structure, the main body is provided with a first side surface layer and a second side surface layer which are opposite to each other, the phase-change material is at least arranged in the pores of the first side surface layer and the pores of the second side surface layer, the phase-change material is sealed in the pores of the aerogel felt and has a heat storage function, and the finally prepared aerogel felt is high in shape thermal conductivity and large in phase-change latent heat and can effectively prevent heat from being transferred among battery monomers, so that the heat transfer efficiency of the battery monomers is improved. Thermal runaway propagation is inhibited, and the fire risk of the battery module is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an aerogel felt and a preparation method thereof, a battery and an electrical device. Background Art

[0002] At present, lithium-ion battery cooling technology can be mainly divided into air cooling, liquid cooling, phase change material cooling, and heat pipe cooling. The air thermal management system has a simple structure, light weight, low energy consumption, and easy maintenance. Its technology is mature and has been applied in commercial vehicles; however, the cooling effect of the air cooling system is poor. When the battery generates a lot of heat, it is easy to cause uneven temperature distribution of the battery pack, and even cannot meet the temperature control requirements, and the natural ventilation cooling system cannot work when the vehicle stops. Liquid cooling has a larger convection heat transfer coefficient and higher cooling capacity, but this battery thermal management system based on liquid cooling requires the addition of complex pipes and pumps and other auxiliary equipment, making the system more complex, heavier and more expensive, and also facing the risk of liquid medium leakage; using the excellent thermal conductivity of the heat pipe, the heat generated by the battery can be quickly taken away to achieve the purpose of cooling the battery. However, the shape of the heat pipe itself limits its use to batteries of specific shapes.

[0003] Currently, phase change material cooling technology has gained popularity due to its simple structure, the absence of complex and large auxiliary equipment, and the absence of additional energy consumption. However, when existing phase change materials are used in battery thermal management systems, they are limited by the performance of the material itself and are prone to leakage problems. In addition, most battery modules that directly embed batteries in phase change materials have low energy density and do not consider the function of phase change materials in inhibiting the propagation of thermal runaway. Therefore, there is an urgent need to develop multifunctional lithium battery thermal management products. Summary of the invention

[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide an aerogel felt to solve the problem that the phase change material itself is limited by its own performance and is prone to leakage, thereby contaminating the battery module. If the gaps between batteries are completely filled with phase change materials to prevent the spread of thermal runaway, the energy density of the battery module will be seriously affected. Therefore, it is necessary to improve the thermal insulation performance of the thermal insulation material between battery cells.

[0005] In order to achieve the above-mentioned objectives, the embodiments of the present application provide an aerogel felt and a preparation method thereof, a battery and an electrical device.

[0006] In some embodiments, the present application proposes an aerogel felt for use in lithium-ion batteries, wherein the aerogel felt includes a main body having a porous structure, the main body having a first side surface layer and a second side surface layer relative to each other, and a phase change material is provided in at least the pores of the first side surface layer and the pores of the second side surface layer.

[0007] In some embodiments, the material of the body includes silica aerogel, a sunscreen, and fiber felt.

[0008] In some embodiments, in the material of the aerogel felt, the mass of the silica aerogel, the sunscreen, the fiber felt and the phase change material is (25-30); (1-2); (25-30); (30-50); and / or,

[0009] The sunscreen comprises at least one of silicon carbide whiskers, silicon carbide particles and silicon carbide fibers; and / or,

[0010] The fiber felt comprises at least one of aluminum silicate fiber felt, glass fiber felt, and mullite fiber felt; and / or,

[0011] The phase change material includes higher aliphatic hydrocarbons, fatty acids and their esters or macromolecules.

[0012] In some embodiments, the aerogel felt has a thickness of 1.5 to 2.5 mm; and / or the first side surface layer has a thickness of 0.4 to 0.6 mm; and / or the second side surface layer has a thickness of 0.4 to 0.6 mm.

[0013] In some embodiments, the aerogel felt has a phase change temperature of 45-58° C. and a phase change latent heat of greater than 230 J / g.

[0014] The present application provides a method for preparing an aerogel felt, and the preparation steps are as follows:

[0015] Providing materials for the main body of the aerogel felt, and mixing and drying the materials for the main body to obtain the main body of the aerogel felt, wherein the main body has a first side surface layer and a second side surface layer opposite to each other;

[0016] Phase change materials are coated on the outer surface of the first side surface layer and the outer surface of the second side surface layer respectively, and are melted by vacuum heating so that the phase change materials penetrate into the pores of the first side surface layer and the pores of the second side surface layer, and are cooled and solidified to form an aerogel felt.

[0017] In some embodiments, the drying comprises at least one of atmospheric pressure drying, supercritical drying and freeze drying; and / or,

[0018] The temperature of vacuum heating melting is 70 to 90°C; and / or,

[0019] The vacuum heating melting time is 2 to 6 hours; and / or,

[0020] The cooling and curing temperature is 50 to 70°C; and / or,

[0021] The cooling and curing time is 5 to 7 hours.

[0022] In some embodiments, the step of "providing a main body material, mixing and drying the silica aerogel, the sunscreen and the fiber felt to obtain the main body of the aerogel felt" includes: the main body material includes silica aerogel, the sunscreen and the fiber felt, wherein,

[0023] mixing a sunscreen agent with a silica aerogel to obtain a sol;

[0024] The fiber felt is immersed in the sol, and the sol is aged and dried to obtain the main body of the aerogel felt.

[0025] An embodiment of the present application provides a battery, comprising a battery cell and the above-mentioned aerogel felt attached to the outer side of the battery cell.

[0026] The present application provides an electrical device, comprising the battery as described above.

[0027] The present application discloses an aerogel felt and a preparation method thereof, a battery and an electrical device. The aerogel felt comprises a main body and a phase change material filled in the main body, wherein the main body has a first surface layer and a second surface layer relative to each other, and the phase change material is arranged near the first surface layer and the second surface layer, so that the phase change material is sealed in the main body pores of the aerogel felt, and has a heat storage function, so that the prepared aerogel felt has high thermal conductivity and large latent heat of phase change. When the lithium-ion battery is charged and discharged daily, the temperature of the battery module can be effectively reduced and the temperature uniformity of the battery module can be improved. When the lithium battery causes thermal runaway due to thermal abuse, it can also effectively prevent the transfer of heat between battery cells, inhibit the propagation of thermal runaway, and reduce the fire risk of the battery module. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a structural schematic diagram of the aerogel felt preparation process in one embodiment of the present application;

[0029] Figure 2 is a schematic diagram of the aerogel felt prepared in Example 1 of the present application;

[0030] Figure 3 This is a SEM image of the aerogel felt obtained in Example 3 of the present invention;

[0031] Figure 4 This is a DMA temperature scanning pattern diagram of the aerogel felt obtained in Example 2 of the present invention;

[0032] Figure 5 Schematic diagram of the high temperature thermal insulation performance test device and results of the aerogel felt obtained in Example 2 of the present invention;

[0033] Figure 6 This is a schematic diagram of the thermocouple arrangement position;

[0034] Figure 7 This is a schematic diagram of the cooling effect of the aerogel felt obtained in Example 1 of the present invention during the battery charging and discharging process;

[0035] Figure 8 A schematic diagram of a battery used to test thermal runaway in Example 1 of the present invention;

[0036] Fig. 9 This is a functional diagram of the composite phase change material obtained in Example 1 of the present invention for inhibiting the propagation of thermal runaway.

[0037] Description of Figure Numbers:

[0038] 1. First side surface layer; 2. Second side surface layer; 3. Main body.

[0039] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0040] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.

[0041] Currently, phase change material cooling technology has gained popularity due to its simple structure, the absence of complex and large auxiliary equipment, and the absence of additional energy consumption. However, when existing phase change materials are used in battery thermal management systems, they are limited by the performance of the material itself and are prone to leakage problems. In addition, most battery modules that directly embed batteries in phase change materials have low energy density and do not consider the function of phase change materials in inhibiting the propagation of thermal runaway. Therefore, there is an urgent need to develop multifunctional lithium battery thermal management products.

[0042] In view of this, an embodiment of the present application proposes an aerogel felt for use in lithium-ion batteries, wherein the aerogel felt includes a main body 3, wherein the main body 3 has a porous structure, wherein the main body 3 has a first side surface layer 1 and a second side surface layer 2 relative to each other, and a phase change material is provided at least in the pores of the first side surface layer 1 and the pores of the second side surface layer 2.

[0043] The present application discloses an aerogel felt and a preparation method thereof, a battery and an electrical device, wherein the aerogel felt comprises a main body and a phase change material filled in the main body 3, wherein the main body 3 has a first side surface layer 1 and a second side surface layer 2 relative to each other, and phase change material is provided at least in the pores of the first side surface layer 1 and the pores of the second side surface layer 2, so that the phase change material is sealed in the pores of the main body 3 of the aerogel felt, and has a heat storage function, so that the prepared aerogel felt has high thermal conductivity and large latent heat of phase change. When the lithium-ion battery is charged and discharged daily, the temperature of the battery module can be effectively reduced and the temperature uniformity of the battery module can be improved. When the lithium battery causes thermal runaway due to thermal abuse, it can also effectively prevent the transfer of heat between battery cells, inhibit the propagation of thermal runaway, and reduce the fire risk of the battery module.

[0044] It should be noted that the battery temperature using phase change material cooling technology is not only significantly lower than that of the battery pack that does not use cooling technology at the rated charge and discharge current, but it can also play a significant cooling role during fast charging and discharging.

[0045] In any embodiment, the material of the main body includes silica aerogel, a sunscreen and a fiber felt, thus constituting the main body of the aerogel felt.

[0046] It should be noted that, due to its nanoscale void structure, the surface tension of the aerogel particles and the capillary force between the pores of the silica aerogel can retain the liquid phase change material in the porous structure of the aerogel. When the ambient temperature exceeds the phase change temperature point, the macroscopic performance of the aerogel felt is that there is no obvious leakage of the liquid phase change material. Therefore, aerogel is feasible as a skeleton support material for phase change materials. Coupled with the excellent thermal insulation performance and thermal stability of aerogel, it has great potential to block the spread of thermal runaway between battery modules, so it can integrate battery cooling and heat propagation barrier functions. In addition, due to its lightweight characteristics, as a thermal insulation material between batteries, it will not significantly affect the energy density of the battery module. The silica aerogel in this embodiment is prepared by itself, and it can be prepared by referring to the preparation method of aerogel in patent number CN 116791358A. It can be used as one of the main materials in the aerogel felt of this application.

[0047] In any embodiment, the sunscreen includes at least one of silicon carbide whiskers, silicon carbide particles and silicon carbide fibers. Using at least one of the above substances can increase the thermal insulation performance of silica aerogel at high temperatures, thereby inhibiting heat transfer at high temperatures.

[0048] In any embodiment, the fiber felt includes at least one of aluminum silicate fiber felt, glass fiber felt, and mullite fiber felt. At least one of aluminum silicate fiber felt, glass fiber felt, and mullite fiber felt is used. Since the fiber felt has flexibility and strong mechanical strength, and has a large number of pores that can be filled with aerogel, it can be used as the skeleton of the aerogel felt.

[0049] In any embodiment, the phase change material includes higher aliphatic hydrocarbons, fatty acids and their esters or polymers, wherein the higher aliphatic hydrocarbons include n-hexadecane, n-octadecane or paraffin; fatty acids and their esters include stearic acid or palmitic acid, and polymers include polyethylene glycol, such as at least one of phase change paraffin, PEG1000 and PEG1500, and of course not limited thereto, as long as the phase change material satisfies the requirement of being able to change from solid to liquid at a certain temperature so as to penetrate into the nanopores of the aerogel, and solidify and seal after cooling, when the phase change point is reached again, macroscopic leakage will not occur due to the limitation of the capillary force on the surface of the aerogel particles, so that the leakage problem of the phase change material can be solved while giving full play to the performance of the phase change material, and preferably, the purity of the phase change paraffin is above 99%, because the phase change paraffin is non-corrosive and can be used in a wide temperature range. Paraffin is relatively stable, can be used for a long time, and has a wide range of uses.

[0050] In any embodiment, in the material of the aerogel felt, the mass ratio of the silica aerogel, the sunscreen, the fiber felt and the phase change material is (25-30); (1-2); (25-30); (30-50). Within this mass ratio range, the temperature of the battery module can be effectively reduced and the temperature uniformity of the battery module can be improved while suppressing the propagation of thermal runaway and reducing the fire risk of the battery module. The silica aerogel, the sunscreen, the fiber felt and the phase change material are preferably selected from the group consisting of: (1) aerogel, (2) aerogel, (3) aerogel, (4) aerogel, (5) aerogel, (6) aerogel, (7) aerogel, (8) aerogel, (9) aerogel, (10) aerogel, (11) aerogel, (12) aerogel, (13) aerogel, (14) aerogel, (15) aerogel, (16) aerogel, (17) aerogel, (18) aerogel, (19) aerogel, (20) aerogel, (21) aerogel, (22) aerogel, (23) aerogel, (24) aerogel, (25) aerogel, (26) aerogel, (27) aerogel, (28) aerogel, (29) aerogel, (30) aerogel, (31) aerogel, (32) aerogel, (34) aerogel, (35) aerogel, (36) aerogel, (37) aerogel, (38) aerogel, (39) aerogel, (40) aerogel, (41) aerogel, (42) aerogel, (43) aerogel, (44) aerogel, (45) aerogel, (46) aerogel, (47) aerogel, (48) aerogel, (49) a 、 The mass ratio of the fiber felt to the phase change material may be 25:1:25:30, 30:2:30:50 or 28:1:28:40.

[0051] Specifically, the main body of the aerogel felt described in the present invention is silicon carbide as a high-temperature sunshade and phase change paraffin as a heat absorption layer, and by optimizing the ratio of each raw material, a solid-liquid phase change material is obtained. The sandwich structure composite phase change material has both the inherent heat storage function of the phase change material and the good thermal insulation performance of the aerogel.

[0052] It should be noted that the amount of phase change material needs to be controlled, and the amount filled into the main body can be controlled. If an excessive amount penetrates into the main body and fills it up, the thermal insulation effect will be lost. Therefore, the amount of phase change material needs to be within a certain range. It only needs to stay in the main body and at least the phase change material is provided in the pores of the first side surface layer and the pores of the second side surface layer. It is best to fill both.

[0053] In any embodiment, the thickness of the aerogel felt is 1.5 to 2.5 mm. Within this thickness range, it can block the spread of thermal runaway, occupy less space, and will not significantly affect the energy density of the battery module. The volume of the phase change material will not expand due to repeated phase changes, and the phase change process will not produce gas to damage the battery module. It is preferably 2 mm, which has a better effect. In addition, the high temperature resistant aerogel felt has certain elasticity and fatigue resistance, and can fit more consistently with the battery cell and the bottom surface of the battery module. When the battery module vibrates, falls or collides, it can provide good protection for the battery cell, thereby improving the safety and environmental adaptability of the battery module.

[0054] In any embodiment, the thickness of the first side surface layer is 0.4-0.6 mm; and / or the thickness of the second side surface layer is 0.4-0.6 mm. Within this range, too thick will affect the energy density, and too thin will also have limited heat dissipation effect.

[0055] In some embodiments, the aerogel felt obtained specifically is as follows Figure 1 As shown, the thickness distribution of aerogel felt for thermal management of lithium-ion batteries: the layers 600 microns downward from the upper surface and 600 microns upward from the lower surface are filled with phase change materials, which are not only filled in the nanopores of the aerogel, but also in the gaps between the aerogel blocks. Therefore, from the results of scanning electron microscopy, it will be denser and have fewer pores. The middle layer with a thickness of about 800 microns contains only aerogel and sunscreen, and of course some fibers of the fiber felt. This layer mainly plays a role of heat insulation. By adsorbing phase change material on the surface aerogel, the heat dissipation and heat insulation functions are integrated on one material to obtain the aerogel felt of this embodiment.

[0056] In any embodiment, the aerogel felt has a phase change temperature of 45-58° C. and a phase change latent heat of greater than 230 J / g.

[0057] Specifically, when the aerogel felt of the present invention is applied to a thermal management system of a lithium-ion battery, its melting point is about 58°C. When the temperature of the lithium-ion battery is higher than 54°C during the charging and discharging process, the heat generated can be quickly absorbed by the phase change material, avoiding side reactions caused by the temperature increase and making the temperature of the battery tend to be consistent, so that the working performance of the lithium-ion battery can be best exerted.

[0058] The present invention also provides a method for preparing an aerogel felt, and the preparation steps are as follows:

[0059] S10, providing materials for the main body 3 of the aerogel felt, and mixing and drying the materials for the main body 3 to obtain the main body of the aerogel felt, wherein the main body 3 has a first side surface layer 1 and a second side surface layer 2 opposite to each other;

[0060] In this embodiment, the fiber felt is used as a skeleton, so that the silica aerogel is distributed between the fibers, and the sunscreen is used to further increase the thermal insulation performance of the silica aerogel at high temperatures, thereby obtaining the main body of the aerogel felt.

[0061] Further, the material of the main body includes silica aerogel, sunscreen and fiber felt, and step S10 includes:

[0062] mixing a sunscreen agent with a silica aerogel to obtain a sol;

[0063] The fiber felt is immersed in the sol, and the sol is aged and dried to obtain the main body of the aerogel felt.

[0064] Specifically, in some embodiments, the operation steps include: adding silicon carbide fiber to silica aerogel, stirring and mixing evenly to obtain a sol, then immersing the fiber felt in the sol, and after gelation and aging, using a supercritical drying method to obtain a high temperature resistant aerogel felt.

[0065] S20, coating the phase change material on the outer surface of the first side surface layer 1 and the outer surface of the second side surface layer 2 respectively, heating and melting in vacuum to allow the phase change material to penetrate into the pores of the first side surface layer 1 and the pores of the second side surface layer 2, cooling and solidifying to form an aerogel felt.

[0066] In this step, the phase change material is sealed in the pores of the main body 3. It will not leak from the main body 3 regardless of being heated or solidified, so it will not corrode the battery. It also does not need to be packaged externally. The volume of the packaged phase change material will not expand due to repeated phase changes, and the phase change process will not produce gas to damage the battery module.

[0067] Specifically, the phase change material of the present invention is applied to the thermal management system of lithium-ion batteries. Its melting point is about 58°C. When the temperature of the lithium-ion battery is higher than 54°C during the charging and discharging process, the heat generated can be quickly absorbed by the phase change material, avoiding the side reactions caused by the temperature increase and making the temperature of the battery tend to be consistent, so that the working performance of the lithium-ion battery can be best exerted.

[0068] In any embodiment, the drying includes at least one of atmospheric pressure drying, supercritical drying and freeze drying; and / or the heating and melting temperature is 70 to 90° C.; and / or the heating and melting time is 2 to 6 hours; and / or the vacuum cooling temperature is 50 to 70° C.; and / or the vacuum cooling time is 5 to 7 hours.

[0069] Here, drying is used to mix the silica aerogel, sunscreen and fiber felt, and the aerogel felt is obtained by drying. Specifically, heating and melting is to melt the phase change graphite, which is evenly loaded on the surface of the main body 3 and placed in a vacuum oven. After the heated phase change graphite is converted into liquid, it penetrates into the nano-scale pores of the main body 3, and is wrapped around the surface of the main body 3 by surface tension and capillary force. After cooling, the aerogel felt is obtained.

[0070] In one embodiment of the present application, a battery is provided.

[0071] Typically, a battery includes a battery cell and an aerogel felt as described above attached to the outer side of the battery cell.

[0072] In addition, the present application also provides an electrical device, which includes the battery provided in the present application. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0073] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0074] Example 1

[0075] An aerogel felt, taking 5g as the standard, comprises: 35% phase change paraffin, 35% fiber felt, 28% silicon dioxide aerogel and 2% silicon carbide fiber.

[0076] The aerogel felt is prepared by the following method:

[0077] Add silicon carbide fiber to silica sol, stir and mix evenly, then immerse fiber felt in the sol, and use supercritical drying method after gelation and aging to obtain aerogel felt, wherein the silica aerogel is prepared according to the preparation method of aerogel in patent number CN 116791358 A;

[0078] The phase-change paraffin wax powder was uniformly loaded on the surface of the aerogel felt, and then placed at 70°C in a vacuum environment for 6 hours and then cooled and solidified;

[0079] The phase-change paraffin wax powder is then evenly loaded on the other side of the aerogel felt, and the same vacuum impregnation operation is performed to obtain the aerogel felt. The macroscopic morphology of the aerogel felt obtained in this embodiment is as follows: Figure 2 shown.

[0080] Example 2

[0081] An aerogel felt, taking 5g as the standard, comprises: 50% phase change paraffin wax, 25% aluminum silicate fiber felt, 24% silicon dioxide aerogel and 1% silicon carbide whisker.

[0082] The aerogel felt is prepared by the following method:

[0083] Add silicon carbide whisker SF-1 to silica sol, stir and mix evenly, then immerse fiber felt in the sol, and use supercritical drying method after gelation and aging to obtain aerogel felt, wherein the silica aerogel is prepared according to the preparation method of aerogel in patent number CN 116791358 A;

[0084] The phase-change paraffin wax powder was uniformly loaded on the surface of the aerogel felt, and then placed at 50°C in a vacuum environment for 6 hours and then cooled and solidified;

[0085] Then, the phase-change paraffin wax powder is evenly loaded on the other side of the aerogel felt, and the same vacuum impregnation operation is performed to obtain the aerogel felt.

[0086] Example 3

[0087] An aerogel felt, taking 5g as the standard, comprises: 40% phase change paraffin wax, 30% glass fiber felt, 25% silicon dioxide aerogel and 2% silicon carbide particles.

[0088] The aerogel felt is prepared by the following method:

[0089] Add silicon carbide particles to the silica sol, stir and mix evenly, then immerse the fiber felt in the sol, and after gelation and aging, use a normal pressure drying method to obtain an aerogel felt, wherein the silica aerogel is prepared according to the preparation method of aerogel in Patent No. CN116791358 A;

[0090] The phase-change paraffin wax powder was uniformly loaded on the surface of the aerogel felt, and then placed at 70°C in a vacuum environment for 6 hours and then cooled and solidified;

[0091] Then, the phase-change paraffin wax powder is evenly loaded on the other side of the aerogel felt, and the same vacuum impregnation operation is performed to obtain the aerogel felt.

[0092] Example 4

[0093] An aerogel felt, taking 5g as the standard, comprises: 40% phase change paraffin, 30% aluminum silicate fiber felt, 30% silicon dioxide aerogel and 2% silicon carbide particles.

[0094] The aerogel felt is prepared by the following method:

[0095] Add silicon carbide particles to the silica sol, stir and mix evenly, then immerse the fiber felt in the sol, and after gelation and aging, use a normal pressure drying method to obtain an aerogel felt, wherein the silica aerogel is prepared according to the preparation method of aerogel in Patent No. CN116791358 A;

[0096] The phase-change paraffin wax powder was uniformly loaded on the surface of the aerogel felt, and then placed at 70°C in a vacuum environment for 6 hours and then cooled and solidified;

[0097] Then, the phase-change paraffin wax powder is evenly loaded on the other side of the aerogel felt, and the same vacuum impregnation operation is performed to obtain the aerogel felt.

[0098] Example 5

[0099] An aerogel felt, measured in mass percentage with 5g as the standard, comprises: 30% phase change paraffin wax, 35% mullite fiber felt, 35% silicon dioxide aerogel and 3% silicon carbide particles.

[0100] The aerogel felt is prepared by the following method:

[0101] Add silicon carbide particles to the silica sol, stir and mix evenly, then immerse the fiber felt in the sol, and after gelation and aging, use a normal pressure drying method to obtain an aerogel felt, wherein the silica aerogel is prepared according to the preparation method of aerogel in Patent No. CN116791358 A;

[0102] The phase-change paraffin wax powder was uniformly loaded on the surface of the aerogel felt, and then placed at 70°C in a vacuum environment for 6 hours and then cooled and solidified;

[0103] Then, the phase-change paraffin wax powder is evenly loaded on the other side of the aerogel felt, and the same vacuum impregnation operation is performed to obtain the aerogel felt.

[0104] Comparative Example 1

[0105] The addition of phase change material was omitted during the preparation process, and the rest was the same as in Example 2 to prepare an aerogel felt.

[0106] Performance Test:

[0107] The aerogel felts of Examples 1 to 5 and Comparative Example 1 were tested as follows:

[0108] 1. Elasticity and variable temperature fatigue resistance test of aerogel felt

[0109] The aerogel felt prepared in Example 2 was selected with a size of 10mm*10mm*10mm as a test sample, an alternating load was applied to the test sample, and the test mode was adjusted to temperature scanning, the frequency was fixed at 1Hz, the deformation was 0.25%, the temperature scanning range was 30-400°C, the response generated by the test sample was recorded, and the dynamic performance parameters of the material such as storage modulus, loss modulus, loss tangent, etc. were output by calculation.

[0110] Test results such as Figure 4 As shown, it can be seen that within the temperature scanning range, the storage modulus, loss modulus and loss tangent do not change significantly within a certain range, indicating that the high temperature resistant aerogel felt has excellent fatigue resistance in a wider temperature range.

[0111] 2. High temperature thermal insulation performance test

[0112] Figure 5 include Figure 5 a and Figure 5 b, using Figure 5 The test device shown in a is used to directly heat the front side of the aerogel felt prepared in Example 2 with a butane torch flame (temperature can reach 1200°C), and the temperature change on the back side of the aerogel felt is measured in real time with an infrared imager. To make the results more convincing, three measuring points (sp1-3, such as Figure 5 b).

[0113] Test results: The temperature on the back of the aerogel felt reaches its highest value in about 4 minutes. As the heat dissipation rate increases after the object temperature rises, the temperature on the back decreases slightly and stabilizes at about 100°C after 10 minutes. The 10mm thick aerogel felt has a temperature gradient of up to 1100°C in the thickness direction, which shows that the aerogel felt has very good thermal insulation performance. Compared with ordinary thermal insulation materials such as mica and foam, it can use a thinner thickness to isolate the same amount of heat.

[0114] 3. Charge and discharge performance test applied to batteries

[0115] The aerogel felt for thermal management of lithium-ion batteries prepared in Example 1 was placed between battery cells, and the battery was charged and discharged with a 1C current. Three 2mm thick K-type thermocouples were used. Figure 6 The arrangement shown is used to measure the temperature of three locations on the battery surface during charging and discharging, where: Figure 6The front side is the side in contact with the aerogel felt for thermal management of lithium-ion batteries, PA@SAS is the aerogel felt for thermal management of lithium-ion batteries, and the back side is the side not in contact with the aerogel felt for thermal management of lithium-ion batteries.

[0116] The test results are from Figure 7 It can be concluded that when no material is used, that is, Figure 7 Blank, the battery surface temperature can reach up to 75.93℃, using only the highest temperature of pure aerogel material, that is Figure 7 The SAS can reach 79.62℃, which is because the good thermal insulation performance of the aerogel prevents the heat of the battery from being lost. The battery using the aerogel felt prepared in Example 1 of the present application, that is, Figure 7 For PA@SAS, the highest battery surface temperature is 64.64°C, and the temperature difference among the three measuring points does not exceed 1.82°C, which fully demonstrates the cooling effect of the phase change material.

[0117] 4. Thermal runaway performance test

[0118] The aerogel felt for thermal management of lithium-ion batteries prepared in Example 1 was placed between battery cells, and the battery (LIB.I) was tested for thermal runaway by an electric heating plate. It should be noted that Figure 8 As shown, there are 5 2mm K-type thermocouples on the surface of each battery to measure the temperature. The battery with thermal runaway is directly triggered by the heating plate (i.e., the battery closest to the heating plate is LIB.I. The thermal runaway starts from LIB.I and propagates in one direction (for example, if the heating plate is on the left side of LIB.I, the thermal runaway propagation direction is to the right), and will propagate to LIBⅡ, LIBⅢ, and LIBⅣ in sequence. There will be an aerogel felt prepared in Example 1 between every two batteries, and the thermal runaway will be triggered when the temperature of the battery (LIB.I) is around 135°C. The aerogel felt prepared in Example 1 and Comparative Example 1 is placed between the battery cells, and the 5 measuring points of each battery are tested respectively.

[0119] Test results such as Fig. 9 As shown: the temperature of the battery prepared in comparative example 1 rises sharply, with a rate of up to 8.5°C / s, but the aerogel felt battery for thermal management of lithium-ion batteries prepared in embodiment 1 of the present invention can limit thermal runaway to the first battery, and the battery protected by the aerogel felt has a temperature rise due to only a small amount of heat transfer, but thermal runaway is not triggered.

[0120] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and playing the same role within the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An aerogel felt for use in a thermal management system for a lithium-ion battery, characterized in that: The aerogel felt comprises a main body having a porous structure, the main body having a first side surface layer and a second side surface layer opposite to each other, and phase change materials are arranged at least in the pores of the first side surface layer and the pores of the second side surface layer.

2. The aerogel felt according to claim 1, characterized in that The material of the main body includes silica aerogel, sunscreen and fiber felt.

3. The aerogel felt according to claim 2, characterized in that: In the material of aerogel felt, the silica aerogel, the sunscreen 、 The mass ratio of the fiber felt to the phase change material is (25-30): (1-2): (25-30): (30-50); and / or, The sunscreen comprises at least one of silicon carbide whiskers, silicon carbide particles and silicon carbide fibers; and / or, The fiber felt comprises at least one of aluminum silicate fiber felt, glass fiber felt, and mullite fiber felt; and / or, The phase change material includes higher aliphatic hydrocarbons, fatty acids and their esters or macromolecules.

4. The aerogel felt according to claim 1, characterized in that: The thickness of the aerogel felt is 1.5 to 2.5 mm; and / or, The thickness of the first side surface layer is 0.4-0.6 mm; and / or, The thickness of the second side surface layer is 0.4-0.6 mm.

5. The aerogel felt according to claim 1, characterized in that: The aerogel felt has a phase change temperature of 45-58° C. and a phase change latent heat of greater than 230 J / g.

6. A method for preparing an aerogel felt according to any one of claims 1 to 5, characterized in that: The preparation steps are as follows: Providing materials for the main body of the aerogel felt, and mixing and drying the materials for the main body to obtain the main body of the aerogel felt, wherein the main body has a first side surface layer and a second side surface layer opposite to each other; Phase change materials are coated on the outer surface of the first side surface layer and the outer surface of the second side surface layer respectively, and are melted by vacuum heating so that the phase change materials penetrate into the pores of the first side surface layer and the pores of the second side surface layer, and are cooled and solidified to form an aerogel felt.

7. The method for preparing aerogel felt according to claim 6, characterized in that: The drying comprises at least one of atmospheric pressure drying, supercritical drying and freeze drying; and / or, The temperature of vacuum heating melting is 70 to 90° C.; and / or, The vacuum heating melting time is 2 to 6 hours; and / or, The cooling and curing temperature is 50 to 70°C; and / or, The cooling and curing time is 5 to 7 hours.

8. The method for preparing aerogel felt according to claim 6, characterized in that: The step of "providing a main body material of the aerogel felt, and mixing and drying the main body material to obtain the main body of the aerogel felt, wherein the main body has a first side surface layer and a second side surface layer opposite to each other" includes: the main body material includes silica aerogel, a sunscreen and a fiber felt, wherein: mixing a sunscreen agent with a silica aerogel to obtain a sol; The fiber felt is immersed in the sol, and the sol is aged and dried to obtain the main body of the aerogel felt.

9. A battery, characterized in that: The invention comprises a battery cell and an aerogel felt as claimed in any one of claims 1 to 8 bonded to the outside of the battery cell.

10. An electrical device, characterized in that: Comprising the battery as claimed in claim 9.

Citation Information

Cited By

  • Diaphragm and preparation method thereof, battery and electric equipment

    CN120109428A